2021
DOI: 10.1101/2021.07.15.452529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LincRNA-Cox2 functions to regulate inflammation in alveolar macrophages during acute lung injury

Abstract: The respiratory system exists at the interface between our body and the surrounding non-sterile environment; therefore, it is critical for a state of homeostasis to be maintained through a balance of pro- and anti- inflammatory cues. An appropriate inflammatory response is vital for combating pathogens, while an excessive or uncontrolled inflammatory response can lead to the development of chronic diseases. Recent studies show that actively transcribed noncoding regions of the genome are emerging as key regula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Since this study, we and others have shown that lincRNA-Cox2 is a highly inflammatory inducible gene that functions broadly to regulate immune genes during the innate immune response. [58][59][60][61][62][63][64] Interestingly, using multiple genetic mice models, we found that lincRNA-Cox2 can function both in cis where it regulates the critical immune gene Ptgs2 (Cox2) through an enhancer RNA mechanism as well as in trans to regulate a wide variety of immune genes in macrophages. 62,63 We found that LincRNA-Cox2 can function in trans to negatively regulate basal expression of interferon-stimulated genes through interactions with hnRNPA2/B1 and hnRNPA/B (Figure 3B).…”
Section: Ln Crna S and Innate Immunit Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study, we and others have shown that lincRNA-Cox2 is a highly inflammatory inducible gene that functions broadly to regulate immune genes during the innate immune response. [58][59][60][61][62][63][64] Interestingly, using multiple genetic mice models, we found that lincRNA-Cox2 can function both in cis where it regulates the critical immune gene Ptgs2 (Cox2) through an enhancer RNA mechanism as well as in trans to regulate a wide variety of immune genes in macrophages. 62,63 We found that LincRNA-Cox2 can function in trans to negatively regulate basal expression of interferon-stimulated genes through interactions with hnRNPA2/B1 and hnRNPA/B (Figure 3B).…”
Section: Ln Crna S and Innate Immunit Ymentioning
confidence: 99%
“…[58][59][60][61][62][63][64] Interestingly, using multiple genetic mice models, we found that lincRNA-Cox2 can function both in cis where it regulates the critical immune gene Ptgs2 (Cox2) through an enhancer RNA mechanism as well as in trans to regulate a wide variety of immune genes in macrophages. 62,63 We found that LincRNA-Cox2 can function in trans to negatively regulate basal expression of interferon-stimulated genes through interactions with hnRNPA2/B1 and hnRNPA/B (Figure 3B). 58 Interestingly, many lncRNAs that function within the immune system appear to do so through interactions with various hnRNP proteins.…”
Section: Ln Crna S and Innate Immunit Ymentioning
confidence: 99%
“…Their abundance in the genome is similar to that of protein-coding genes, and many have been shown to contribute to various phenotypes through interactions with proteins, RNA, DNA, or combinations thereof [6,7]. Although only a few per cent of catalogued lncRNAs have been characterized, those that have are implicated in key biological processes including immunity [8,9], cancer [10], viability, and differentiation [6,7]. LncRNAs are often processed similarly to mRNAsspliced, capped, and adenylatedand those that are exported to the cytoplasm are frequently found bound to ribosomes.…”
mentioning
confidence: 99%